Redefining Learning Outcomes in Higher Education through Centers for Teaching and Learning - Nouri, Venetia (Adult Education Critical Issues, 2025)
This paper critically examines the role of Centers for Teaching and Learning (CTLs) in enhancing learning outcomes within higher education institutions. CTLs are pivotal in fostering effective teaching environments, enhancing faculty capabilities, and ultimately improving student learning outcomes. The paper delves into the theoretical underpinnings that inform CTL practices, highlighting the influence of adult learning theories, transformative learning, and critical pedagogy on faculty development initiatives. It assesses CTLs’ strategies in course design and student assessment, discussing the practical challenges such as funding limitations and resistance to pedagogical shifts. Moreover, it explores the broader implications of CTLs on institutional policies and the integration of technology in teaching. The paper proposes strategic enhancements for CTLs, including increased funding, policy reform, and leveraging international collaborations to enrich teaching practices. Through a comprehensive analysis of CTLs’ impact on learning outcomes, the paper underscores their indispensable role in the continuous evolution of higher education.